DINAMIKA POLITIK MASA REVOLUSI: PERBEDAAN PANDANGAN ELITE PUSAT DENGAN ELITE JAWA TIMUR - Ari Sapto (Jurnal Sejarah dan Budaya, 2013)
Abstract. Defined as main problem nowadays, relationship between disctrict prefecture and central government have not done yet. Identified by many years ago, this problem has emerged during Independence revolution periods. Direction, purposes and through revolution path have became discussion between elite ended with contradiction. It was caused by different sightseeing of the other elites on East Java. Powerful effects of politics reality, East Java culture and self interest influence rationale thoughts